2009
DOI: 10.3945/ajcn.2008.27411
|View full text |Cite
|
Sign up to set email alerts
|

Skim milk compared with a fruit drink acutely reduces appetite and energy intake in overweight men and women

Abstract: Background: Several studies show that proteins, including whey and casein, are more satiating than carbohydrates. It follows that skim milk would be more satiating than sugar-rich beverages. However, this has yet to be shown. Objective: The objective was to investigate the effects of drinking skim milk in comparison with a fruit drink at breakfast on selfreported postmeal satiety and energy intake at lunch. Design: In a randomized crossover trial, 34 overweight women (n = 21) and men (n = 13) attended 2 sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 34 publications
(40 reference statements)
4
75
0
2
Order By: Relevance
“…Dove et al (2009) found that 600 ml of skim milk with 25 g protein reduced the EI at the following meal by 8.6% corresponding to a difference of 226 kJ (Po0.05) compared with isocaloric fruit juice. However, in agreement with our results DellaValle et al (2005) found no changes in EI between regular cola, fruit juice or milk (1% fat) after the volunteers consumed 360 g of the various beverages together with a meal.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Dove et al (2009) found that 600 ml of skim milk with 25 g protein reduced the EI at the following meal by 8.6% corresponding to a difference of 226 kJ (Po0.05) compared with isocaloric fruit juice. However, in agreement with our results DellaValle et al (2005) found no changes in EI between regular cola, fruit juice or milk (1% fat) after the volunteers consumed 360 g of the various beverages together with a meal.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Soenen and Westerterp-Plantenga (2007) found similar effects of milk and SSSD on appetite sensations in a 140-min intervention. The different results may be because of the fact that the effect of milk on satiation sensations and subsequently on EI grows over time and is most pronounced after 2 h or longer after the milk intake (Anderson et al, 2004;Dove et al, 2009). Dove et al (2009) performed a study rather like ours with a test drink followed by an ad libitum meal 4 h later.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations